Hiding Mengele : how a Nazi network harbored the Angel of Death - Anton, Betina (Diversion Books, 2024)
Josef Mengele, known worldwide for unimaginably cruel human experiments and for sending thousands of people to the gas chambers at Auschwitz, was a fugitive in South America for thirty-four years after World War II, sought by the Israeli secret service and Nazi hunters. Hidden for half that time in Brazil, Mengele created his own paradise, a life where he could speak German, maintain his beliefs, his friends, and his connection with the homeland. Never caught, he lived out the rest of his days thanks to a small circle of expatriate Europeans willing to help him. One such person was Austrian ex-pat Liselotte Bossert, who buried Mengele with false documents to keep his true identity hidden even after his death in 1979. When the world finally discovered where the remains of Josef Mengele were in 1985, kindergarten teacher Liselotte was escorted from the São Paulo school without further explanation to the students. One six-year-old, Betina Anton, could not let this mystery go. Decades later as an experienced journalist, Betina decided to investigate, but when she found Liselotte, she could not imagine how deep this case would take her.